The euro crisis. A reflection on austerity policies and the institutional design of the european economic and monetary union - Oyarzun, Javier (Papeles de Europa, 2015)
The euro crisis has been analysed in depth since, with Greece’s bailout in early 2010, the Economic and Monetary Union (EMU) imposed severe austerity policies to a set of peripheral countries. The uniqueness of the EMU response to the crisis was due, in a large measure, to its institutional design and the relationship of forces that have operated within, since its inception in 1992 and its start in 2000. This article analyses the causes of the adoption of this policy and studies the main arguments presented by its promoters. The main conclusion in this regard is that the institutional design of EMU is profoundly asymmetrical and the applied austerity policy has benefited almost exclusively the creditor countries and certain economic groups. This policy has proven to be very harmful to the majority of the European population.
Keywords: Economic and Monetary Union (EMU); austerity policy; institutional design; market failure; creditor countries